Ultrasonographic Investigation of Human Fetus Responses to Maternal Communicative and Non-communicative Stimuli - Ferrari, Gabriella A.; Nicolini, Ylenia; Demuru, Elisa; Tosato, Cecilia; Hussain, Merhi; Scesa, Elena; Romei, Luisa; Boerci, Maria; Iappini, Emanuela; Dalla Rosa Prati, Guido; Palagi, Elisabetta; Ferrari, Pier F. (Frontiers in Psychology, 2016)
During pregnancy fetuses are responsive to the external environment, specifically to maternal stimulation. During this period, brain circuits develop to prepare neonates to respond appropriately. The detailed behavioral analysis of fetus’ mouth movements in response to mothers’ speech may reveal important aspects of their sensorimotor and affective skills; however, to date, no studies have investigated this response. Given that newborns at birth are capable of responding with matched behaviors to the social signals emitted by the caregiver, we hypothesize that such precocious responses could emerge in the prenatal period by exploiting infants’ sensitivity to their mother’s voice. By means of a two-dimensional (2D) ultrasonography, we assessed whether fetuses at 25 weeks of gestation, showed a congruent mouth motor response to maternal acoustic stimulation. Mothers were asked to provide different stimuli, each characterized by a different acoustic output (e.g. chewing, yawning, nursery rhymes, etc.) and we recorded the behavioral responses of 29 fetuses. We found that, when mothers sang the syllable LA in a nursery rhyme, fetuses significantly increased mouth openings. Other stimuli provided by the mother did not produce other significant changes in fetus’ behavior. This finding suggests that fetuses are sensitive only to specific maternal vocalizations (LA) and that fetal matched responses are rudimentary signs of early mirroring behaviors that become functional in the postnatal period. In conclusion, fetuses seem to be predisposed to respond selectively to specific maternal stimuli. We propose that such responses may play a role in the development of behavioral and emotional attunement with their mothers long before birth.